Cognitive Bias and Organizational Inertia are Two Functions of Strategic Change An Experimental Study in Amman Stock Market - الصياح, عبد الستار مصطفى (Journal of Economics and Administrative Sciences, 2015)
The research aims at considering the reality of cognitive bias and organizational inertia as determinants of strategic change in a sample of companies listed in Amman Stock Market. To achieve objectives of the research, a model consisting of two independent variables has been designed, namely:(1) The cognitive bias resulting from (escalating commitment, analogy, previous assumptions, representative generalization, command and control, convergent thinking), and (2) Organizational inertia due to (Icarus discrepancy, power distribution, rooted organizational culture), and a dependent variable, strategic change in (leadership patterns, strategy, the organization per se). From the model two main hypotheses were derived; the first concerned with correlations , and the second with effects. Data was collected from a stratified random sample of 200 people at  the top management level working in 20 companies using a questionnaire featured with high honesty and consistency. Correlation  hypotheses were tested based on the correlation coefficient Spearman, and the Effect based on multiple linear regression, and in confidence limit (0.05 ≤ p ). Results demonstrated the existence of strong effects and linkages having statistical implication between cognitive bias and organizational inertia with strategic change. We have found important evidence on the prevalence of cognitive bias and to a lesser extent the organizational inertia, as well as tendency to hesitation and lack of change. Finally, we found a different variation in terms of type, magnitude and direction at the level of variables and sample. The research concluded an integrated applied model of strategic change we think it greatly benefits companies